Use of face masks and heart rate in adults aged 18 to 60 years - Salazar Cáceres, Guillermo Ulises (2022)
Objective. To evaluate the influence of the use of face masks on resting heartrate (HR) and physical activity in adults aged 18 to 60 years, in the city of Lima, during the COVID-19 pandemic in 2020. Methods. An experimental, analytical, prospective and cross-sectional study was carried out. For data collection, a virtual survey was carried out via Google Forms, with a series of questions and indications for the correct measurement of HR in different situations: at rest, immediately after activity and 5 min after physical activity with and without the use of masks (KN95, fabric, surgical and N95). For the present study, the possible causes of increased HR were analyzed, so 60 asymptomatic adults, 40 women and 20 men, in the age range of 18 to 60 years, were selected. Results. It was found that the difference in mean HR with and without mask use immediatelyafter physical activity increased signifcantly depending on the type of mask. With respect to the KN95, an increase of up to 9.6 beats/min was observed, while the fabric, surgical and N95 masks showed an increase of 5.9, 5.6 and 7.4 beats/min, respectively, under the same conditions, calculating an average of 112.7 beats/min over 10.6 beats/min at rest, showing an increase of up to 7% of its value at rest. Results. It was obtained that the difference in the average HR with and without mask use immediately after physical activity increased signifcantly depending onthe type of mask. With respect to KN95, an increase of up to 9,6 beats/min was observed, while cloth, surgical and N95 masks showed an increase of 5,9, 5,6 and 7,4 beats/min, respectively, under the same conditions, calculated at an averageof 112.7 beats/min over 10,6 beats/min at rest, evidencing an increase in up to 7 % of their value at rest. Conclusion. It was found that the use of the face mask exerts a notable influence on HR, immediately and 5 minutes after the end of the physical activity, being the KN95 the most used face mask and the one with the greatest influence on the cardiac pulse.